2024
DOI: 10.3390/informatics11010008
|View full text |Cite
|
Sign up to set email alerts
|

Topic Extraction: BERTopic’s Insight into the 117th Congress’s Twitterverse

Margarida Mendonça,
Álvaro Figueira

Abstract: As social media (SM) becomes increasingly prevalent, its impact on society is expected to grow accordingly. While SM has brought positive transformations, it has also amplified pre-existing issues such as misinformation, echo chambers, manipulation, and propaganda. A thorough comprehension of this impact, aided by state-of-the-art analytical tools and by an awareness of societal biases and complexities, enables us to anticipate and mitigate the potential negative effects. One such tool is BERTopic, a novel dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies have shown that BERTopic can uncover related topics around specific terms, providing deeper insights [18]. It also allows for hierarchical topic reduction and has advanced search and visualization capabilities [19]. However, for longer texts or smaller datasets, LDA and NMF may still be preferable due to their simplicity and lower resource requirements.…”
mentioning
confidence: 99%
“…Studies have shown that BERTopic can uncover related topics around specific terms, providing deeper insights [18]. It also allows for hierarchical topic reduction and has advanced search and visualization capabilities [19]. However, for longer texts or smaller datasets, LDA and NMF may still be preferable due to their simplicity and lower resource requirements.…”
mentioning
confidence: 99%